Oral Presentations Abstracts: ATTITUDES AND OPINIONS OF MEDICAL STUDENTS AND HEALTH CARE PROFESSIONALS ABOUT THE COVID-19 VACCINE (A QUANTITATIVE STUDY FROM A MEDICAL SCHOOL AND ITS AFFILIATED HOSPITALS) - ULMAN, Yesim Isil; ABBASZADEH, Arshiya; AY, Beril; DOGRUCAM, Diyar; DIKEC, Mirkan; AL-AMOUDI, Shahad; DEMIR, Yaren Nur; SENAY, Sahin (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Objectives: Vaccination is one of the most effective scientific inventions to prevent infectious diseases worldwide. Despite the evidence on the efficacy of vaccinations, vaccine refusal still poses a threat for human health. This study aims, firstly, to detect the underlying reasons of vaccine hesitancy concerning the COVID-19 among medical students and healthcare professionals; and, secondly, to compare the results between the two groups. Methods: This is an online, ongoing cross-sectional quantitative study based on a scale validated in the socio-cultural context in Turkey. The sample consists of students of medicine at six years of education including preparatory class at a foundation university in Istanbul, as well as the healthcare professionals at the affiliated hospitals of the same university. Data will mainly be collected through the Scale of Vaccine Hesitancy (1) annexed with demographic and open-ended questions detecting opinions about vaccination. T-test and chi-square tests will be used for the analysis of scale scores and demographic questions respectively. The open-ended questions will provide deeper findings on the issue. Discussion and Conclusion: While COVID-19 pandemic remains a global challenge, vaccine roll-out seems to be the best response to combat the disease. However, reluctance in acceptance of vaccines among diverse populations creates a risk for herd immunity. Comparatively investigating the motives of vaccine hesitancy among health-related populations may help proposing social, ethical guidance for medical education and health policies. Source: Kilincarslan, M. et al (2020). Development of Valid and Reliable Scale of Vaccine Hesitancy in Turkish Language. Konuralp Tıp Dergisi, 12(3), 420-429.